The image of a politician in crisis conditions. Willy Brandt in Polish journalism of the communist era - Patecka-Frauenfelder, Anna (Koszty współczesnych kryzysów, 2021)
The aim of the article is to analyze the political discourse conducted in the press and journalism of the People’s Republic of Poland (1956–1989) about the West German politician Will Brandt. The research assumed the hypothesis that the positive image of the chancellor in Polish discourse resulted from the legitimization needs of the authorities, and more broadly from the confirmation of the rightness of the prevailing socialist ideology. The paper adopts the qualitative method and uses critical discourse analysis (CDA). The bases for the analyses were taken from press texts and journalistic publications representing various worldviews in Poland at the time (1956–1989), which were allowed by the regime. Brandt himself played a decisive role in shaping a positive image of a West German politician in the Polish press, appreciated all over the world for the effective implementation of Ostpolitik, and after 1981 for his attitude towards communist power and solidarity movements. In crisis and breakthrough situations, Brandt’s image as a recognized Western politician was used after 1970 in order to emphasize the rightness of the policy pursued. The created discourse was to develop the feeling that the agreements implemented through it are the only possible solution for Polish-German relations.